2020
DOI: 10.1017/s0022029920000928
|View full text |Cite
|
Sign up to set email alerts
|

Simmental × Holstein crossbred: comparison of immunological traits with parental breeds during peripartum and early lactation period

Abstract: The experiment described in this research communication aimed to compare the immunological traits of Simmental (sire) × Holstein (dam) crossbred cows with the two parental breeds in the peripartum and early lactation period and to estimate the effects of heterosis for these traits. Flow cytometric evaluation of leukocyte subpopulations was assessed in 16 Crossbred (CR), 8 Holstein (HO) and 8 Simmental (SI) cows. Estimated average values of innate and adaptive immune cells showed statistically significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…At the time of calving we found a particular increase of glucose in HO with respect to the other breeds. This finding could be related to the higher value of granulocyte, neutrophil and monocyte proportions at calving found in the HO compared to SI and CR in our previous work (Scatà et al ., 2020). Indeed, glucose is required by phagocytic cells for proliferation, survival and differentiation, and has been shown to be the preferred metabolic fuel during inflammation for activated PMN, macrophages and lymphocytes (Ingvartsen and Moyen, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of calving we found a particular increase of glucose in HO with respect to the other breeds. This finding could be related to the higher value of granulocyte, neutrophil and monocyte proportions at calving found in the HO compared to SI and CR in our previous work (Scatà et al ., 2020). Indeed, glucose is required by phagocytic cells for proliferation, survival and differentiation, and has been shown to be the preferred metabolic fuel during inflammation for activated PMN, macrophages and lymphocytes (Ingvartsen and Moyen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study involving the same groups of cows, we found that CR and SI showed a better ability to restore immune homeostasis after calving with respect to HO. This last group showed altered levels of cellular immunological traits at calving and in early lactation (Scatà et al ., 2020). Furthermore, in the same study, after the evaluation of heterosis for cellular immunological traits we identified an improved activation of humoral immune response and a better ability to restore immune homeostasis after calving in SI × HO crossbred cows with respect to parental breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crossbreeding in dairy cattle serves mainly for the improvement of functional traits and milk composition of Holstein herds [1][2][3][4][5][6] or uses beef-breed sires over dairy cows to increase income from sales of the beef-cross-dairy calves born on the dairy farm [7]. The majority of these studies, however, report only the results of the first crossbreeding generation (F1) in comparison with the purebred line(s), such as e.g., [8,9] for Holstein-Jersey, or [10] for Holstein-Montbeliarde and Holstein-Viking Red, [11] for Holstein-Gir, or [12] for Holstein-Simmental cows. Only the F1 can reach the maximum heterosis effect, which might improve the performance for most trait complexes, e.g., productivity, efficiency, reproduction, and/or vitality of the F1 offspring by surpassing the average of the parental lines [13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies evaluated Holstein × Montbeliarde, Holstein × Jersey or Holstein × Simmental crossbred cows in comparison with one of the parental breeds (most often Holstein) [4,[32][33][34]. Only a very few studies compared crossbred Holstein × Simmental cows and both parental breeds [12,35]. Scata et al [12], for example, compared the immunologic status of the cows.…”
Section: Introductionmentioning
confidence: 99%